Combination Low-Dose Tissue-Type Plasminogen Activator Plus Annexin A2 for Improving Thrombolytic Stroke Therapy - Jiang, Yinghua; Fan, Xiang; Yu, Zhanyang; Liao, Zhengbu; Wang, Xiao-Shu; van Leyen, Klaus; Sun, Xiaochuan; Lo, Eng H.; Wang, Xiaoying (Frontiers in Cellular Neuroscience, 2015)
Risk of hemorrhagic transformation, incomplete reperfusion, neurotoxicity and a short treatment time window comprise major challenges for tissue plasminogen activator (tPA) thrombolytic stroke therapy. Improving tPA therapy has become one of the highest priorities in the stroke field. This mini review article focuses on our recent efforts aimed at evaluating a novel combination approach of low-dose tPA plus recombinant annexin A2 (rA2, a tPA and plasminogen co-receptor), that might enhance tPA thrombolytic efficacy, while reducing its associated complications related to intracerebral hemorrhagic (ICH) transformation. Results of our experimental studies using a focal embolic stroke model in rats support the feasibility of the combination approach and suggest the potential for successful clinical translation.